2022
DOI: 10.1111/1759-7714.14713
|View full text |Cite
|
Sign up to set email alerts
|

Anlotinib plus chemotherapy for T790M‐negative EGFR‐mutant non‐sqNSCLC resistant to TKIs: A multicenter phase 1b/2 trial

Abstract: Background This multicenter phase 1b/2 trial aimed to explore the maximum tolerated dose (MTD), activity, and safety of anlotinib plus chemotherapy in patients with T790M‐negative epidermal growth factor receptor ( EGFR )‐mutant advanced nonsquamous non‐small cell lung cancer (NSCLC) after resistance to first‐ or second‐generation EGFR tyrosine kinase inhibitors (TKIs). Methods In the phase 1b stage, patients received anlotinib (8/10/12 mg, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Anlotinib is an oral small molecule inhibitor of multi-receptor tyrosine kinases, and it targets VEGFR1, VEGFR2, VEGFR3, c-Kit, PDGFR-α, FGFR1, FGFR2, and FGFR3, which can inhibit tumor angiogenesis and cell proliferation ( 14 - 17 ). Wang et al and others have shown that clinically, anlotinib combined with chemotherapy can further improve the efficacy ( 10 , 18 , 19 ). In the study of Zhu et al , it is more cost effective to use anlotinib for patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Anlotinib is an oral small molecule inhibitor of multi-receptor tyrosine kinases, and it targets VEGFR1, VEGFR2, VEGFR3, c-Kit, PDGFR-α, FGFR1, FGFR2, and FGFR3, which can inhibit tumor angiogenesis and cell proliferation ( 14 - 17 ). Wang et al and others have shown that clinically, anlotinib combined with chemotherapy can further improve the efficacy ( 10 , 18 , 19 ). In the study of Zhu et al , it is more cost effective to use anlotinib for patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical trials are currently underway to assess its efficacy in various malignancies, including non-small cell lung cancer, soft tissue sarcomas, and medullary thyroid carcinoma. 15 19 …”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical trials are currently underway to assess its efficacy in various malignancies, including non-small cell lung cancer, soft tissue sarcomas, and medullary thyroid carcinoma. [15][16][17][18][19] Herein, we present the case of a patient with recurrent and metastatic PC with an epidermal growth factor receptor (EGFR) p.L858R (c. T2573G)-sensitizing mutation who responded to anlotinib after failure to respond to gefitinib and everolimus. This report provides new insights into the treatment of metastatic PC in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Anlotinib is a multi-target tyrosine kinase inhibitor (TKI) with potent inhibition activities against VEGFR2/3, FGFR 1-4, PDGFR 𝝰/β, c-Kit, and Ret at the nanomole level. Multiple clinical trials are underway to assess its e cacy in various malignancies, including non-small cell lung cancer (NSCLC), soft tissue sarcomas, and medullary thyroid carcinoma [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%